JA:2021-16. A Roadmap for Delivering Child Care in Agricultural Communities. Issue 3 (2nd July 2020) - Liebman, Amy; Salzwedel, Marsha; Simmons, Juliana; Kruse, Katherine; Lee, Barbara
ABSTRACT: Purpose : The "Protecting Children While Parents Work in Agriculture" project aims to establish safe and nurturing environments for farmworker children while their parents work. Access to good child care aids worker recruitment, improves retention, and boosts morale. However, childcare services are sometimes nonexistent, cost prohibitive, or not available when needed. Ensuring adequate services is best accomplished when childcare providers, agricultural employers, and farmworker parents work together. The Roadmap for Delivering Child Care in Agricultural Communities ( Roadmap ) was developed to facilitate this collaboration. Results/Findings : This project conducted focus groups, surveys, and interviews with agribusiness representatives, childcare providers, and farmworker parents. This formative research found that 90% of surveyed agribusinesses believe providing childcare services to employees' children fosters a more stable workforce, improves employee morale, and enhances company reputation. About half indicated they need guidance on how to implement these services. Interviews with childcare providers indicated that access to child care could improve with representation by the grower community. Farmworker parents stated they were more likely to choose a job in a location with childcare services, and more women would choose to work if child care was available. With these findings, the project team drafted the Roadmap, a step-by-step guide for developing childcare facilities and improving existing childcare services and access to services. It also includes evidence supporting successful agricultural safety and health interventions and how adequate child care is a beneficial investment for agribusinesses and farmworkers alike. It was reviewed by childcare providers, growers, and farmworker advocates, who all agreed the Roadmap is a useful resource they recommend to others. The project team used their feedback to refine the Roadmap language and content and provide recommendations for dissemination. To promote this to key stakeholders, the team developed a promotional video, social media toolkit, and a media release. Practical Application : Growers and other stakeholders can use the Roadmap to facilitate improved access to childcare services for their employees, including creating new childcare options. Stakeholders are encouraged to distribute this handbook in regions with large numbers of hired agricultural workers and to facilitate linkages between growers and childcare providers.